Hyperglycaemia-Linked Diabetic Foot Complications and Their Management Using Conventional and Alternative Therapies - Prawej Ansari; Samia Akther; Joyeeta T. Khan; Sara S. Islam; Md. Samim R. Masud; Anisur Rahman; Veronique Seidel; Yasser H. A. Abdel-Wahab (Applied Sciences, 2022)
Diabetes mellitus, a major cause of mortality around the globe, can result in several secondary complications, including diabetic foot syndrome, which is brought on by diabetic neuropathy and ischemia. Approximately 15% of diabetic patients suffer from diabetic foot complications, and among them 25% are at risk of lower limb amputations. Diabetic foot ulcers are characterized as skin lesions, gangrene, or necrosis, and may develop due to several reasons, including hyperglycemia and slower wound healing in diabetic patients. A management protocol involving wound cleaning, oral antibiotics, skin ointments, and removing dead tissue is currently followed to treat diabetic foot ulcers. In severe cases, amputation is performed to prevent the infection from spreading further. The existing therapy can be costly and present adverse side effects. Combined with a lack of vascular surgeons, this ultimately results in disability, especially in developing nations. There is a growing interest in the use of alternative therapies, such as medicinal plants, to discover more efficient and affordable treatments for diabetic foot syndrome. It has been observed that treatment with numerous plants, including Carica papaya, Annona squamosa, Catharanthus roseus, and Centella asiatica, promotes wound healing, reduces inflammation, and may decrease the number of amputations. However, little information is currently available on the prevention and management of diabetic foot ulcers, and additional research is necessary to completely understand the role of alternative therapies in the treatment of diabetic foot complications.